Water and Diabetes: Prevention and Cure - Kalra, Sanjay; Agrawal , Navneet; Kapoor, Nitin (Journal of the Pakistan Medical Association, 2023)
Water is ubiquitous in nature, and that is why, perhaps, it is not viewed as a nutrient. In the context of diabetes, water intake may have implications in increasing insulin resistance, development of complications, relation to anti-diabetic agents and also in prevention of diabetes. In this brief article, we list various aspects of water nutrition, i.e., hydration that support its status as a mega- nutrient, as a preventative therapy against diabetes, and as a treatment modality for diabetes and its complications. Keywords: Diabetes, diet, H2O, heart failure, hyperglycemia, hyperosmolar coma, ketoacidosis, medical nutrition therapy, nephropathy, renal failure